Field‐Effect Transistors: Ambipolar Triple Cation Perovskite Field Effect Transistors and Inverters (Adv. Mater. 8/2017). Issue 8 (February 2017) - Yusoff, Abd. Rashid bin Mohd.; Kim, Hyeong Pil; Li, Xiuling; Kim, Jeongmo; Jang, Jin; Nazeeruddin, Mohammad Khaja
Abstract : In conventional transistors, silicon is undoubtedly an ideal material, because electrons flowing through the circuitry encounter low amounts of resistance, yet approaching its fundamental barrier. This leads to research into alternative materials such as perovskite. Ambipolar perovskite fieldeffect transistors and inverters with balanced mobilities are demonstrated in article number 1602940 by Jin Jang, Mohammad Khaja Nazeeruddin and co‐workers.